A guide to Peril Strait and Wrangell Narrows, Alaska - Hopkins, William Morgan, author; University of Alaska Press, publisher (Colorado State University. Libraries, 2020)
Learning how to pilot a ship through Wrangell Narrows and Peril Strait is not an easy matter for a vessel operator new to the area, or even for those with experience. It takes time, patience, and a certain appetite for risk. The older generation of captains knew the channels in great detail, but they did not write anything down to leave for the next generation coming up through the ranks. Recognizing the wealth of the knowledge these navigators possessed in their memories, William Hopkins decided to document their charts and methods as he himself learned to maneuver ships through these important and narrow southeastern Alaska channels. A now retired captain who logged many voyages, Hopkins delineates the navigable courses for passing these treacherous waterways in this essential guide.--Provided by publisher.
Peril Strait -- Introduction to Peril Strait -- Navigating Peril Strait -- General -- Securité Calls on VHF Channels 13 and 16 -- Radar Range Scales -- Maxims -- Limitations -- Currents -- Charts and Publications -- General Interest -- Channel Depths -- Weather -- Russian Place Name Lexicon -- Commercial and Sport Fishing -- Range Bearings -- Hydrographic Surveys -- General Precautions -- Inbound to Sitka -- Deadman Reach -- Adams Channel -- Sergius Narrows -- Kakul Narrows -- Salisbury Sound -- Neva Strait -- Whitestone Narrows -- Olga Strait -- Starrigavan Bay -- Outbound from Sitka -- Starrigavan Bay -- Olga Strait -- Whitestone Narrows -- Neva Strait -- Salisbury Sound -- Kakul Narrows -- Sergius Narrows -- Adams Channel -- Deadman Reach -- Sitka Sound Routes -- Big Gavanski Island Light to Sitka Harbor or to the Eastern Anchorage near Jamestown Bay via the Western Channel -- The Eastern Anchorage near Jamestown Bay to Big Gavanski Island Light via the Western Channel -- Cape Edgecumbe to the Eckholms Light -- Eckholms Light to Cape Edgecumbe Light -- Vitskari Island Light to Big Gavanski Island Light and Starrigavan Bay -- Starrigavan Bay to Big Gavanski Island and Vitskari Island Light -- Vitskari Island to Makhnati Rock Buoy 2 and the Western Channel -- Wrangell Narrows -- Introduction to Wrangell Narrows -- Navigating Wrangell Narrows -- General -- Securité Calls on VHF Channels 13 and 16 -- Radar Range Scales -- Maxims -- Limitations -- Currents -- Charts and Publications -- General Interest -- Channel Depths -- Weather -- Regulations -- Commercial and Sport Fishing -- Range Bearings and Reciprocals -- Hydrographic Surveys -- General Precautions -- Northbound Passage -- Southbound Passage.
Keywords: Pilot guides -- Alaska; Wrangell Narrows (Alaska) -- Navigation; Peril Strait (Alaska) -- Navigation